2021
DOI: 10.1155/2021/5692039
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacological Study of Achyranthis bidentatae Radix Effect on Bone Trauma

Abstract: Purpose. Bone trauma is a clinical condition that afflicts the majority of the world’s population. For the management of bone trauma, the underlying mechanisms of the drugs effective for bone healing are deemed necessary. Achyranthis bidentatae Radix (ABR) is a popular alternative medicine recommended in the treatment of bone trauma and injury, yet its mechanism of action persists to be vague. This study was conducted for the evaluation of the mode of action of ABR through network pharmacology in treating bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Radix paeoniae rubra can substantially improve the function of vascular endothelial cells and promote microcirculation[ 32 ]. Achyranthis bidentate radix has antioxidant and anti-inflammatory properties and promotes wound healing and angiogenesis[ 33 ]. Angelica sinensis radix contains ligustilide, which has a positive effect in chronic inflammatory pain.…”
Section: Discussionmentioning
confidence: 99%
“…Radix paeoniae rubra can substantially improve the function of vascular endothelial cells and promote microcirculation[ 32 ]. Achyranthis bidentate radix has antioxidant and anti-inflammatory properties and promotes wound healing and angiogenesis[ 33 ]. Angelica sinensis radix contains ligustilide, which has a positive effect in chronic inflammatory pain.…”
Section: Discussionmentioning
confidence: 99%
“…Research on RAB in modern medicine mostly focused on its pharmacological effects on the bone metabolism, nervous system, and immune system; joint-protection properties; and antioxidation and antitumor effects ( He et al, 2017 ). Using a bioinformatics-based approach, the mechanisms underlying the effects of RAB in the treatment of diseases such as rheumatic arthritis ( Fu et al, 2021 ), osteoarthritis ( Zhang et al, 2020 ), bone trauma ( Wu et al, 2021 ), and breast cancer ( Ju et al, 2021 ) have been elucidated. Nevertheless, the understanding of pathology still differs between traditional and modern medicines, as the terms used for diseases are not identical between the two fields.…”
Section: Introductionmentioning
confidence: 99%
“…ABR, the dry root of Achyranthes bidentata Bl, is considered an important medicine for decongestion, smooth meridians, nourishing the liver and kidney, and strengthening bones (Yang et al, 2019). It is often used to treat waist and knee pain and muscle and bone weakness (Wu et al, 2021). Our previous studies have shown that ABR extract can help improve the bone quality and trabecular structure of rats, inhibit the loss of bone mineral density, inhibit bone resorption and promote bone formation (Lu et al, 2021; Wang et al, 2021; Yang & Zeng, 2021; Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%